PENGARUH BUDAYA ORGANISASI, KOMUNIKASI INTERPERSONAL DAN KOMPETENSI TERHADAP KINERJA GURU SMP NEGERI 34 KERINCI - Faisal Amri (Bussman Journal : Indonesian Journal of Business and Management, 2022)
This study aims to determine the effect of organizational culture, interpersonal communication and competence on the performance of teachers of SMP Negeri 34 Kerinci partially and simultaneously. The respondents of this study were 47 teachers at SMP Negeri 34 Kerinci. By performing multiple linear regression test, coefficient of determination, F statistical test (simultaneous) and t statistical test (partial). The results of the research Organizational Culture have a positive and significant effect on the Teacher Performance of SMPN 34 Kerinci, this is evidenced by t count> t table (2,219> 2,01669) and with a significance value of 0.032 <0.050. Interpersonal communication has a positive and significant effect on teacher performance at SMPN 34 Kerinci, this is evidenced by t count> t table (2.255> 2.01669) and with a significance value of 0.029 <0.050. Competency has a positive and significant effect on teacher performance, SMPN 34 Kerinci, this is evidenced by t arithmetic> t table (6.223> 2.01669). Organizational culture, interpersonal communication and competence simultaneously have a significant effect on teacher performance, this is evidenced by F count> F table (21.932> 2.82), so Ho is rejected and H4 is accepted, and with a significant value (0.000 <0.05). The amount of influence of Organizational Culture on Teacher Performance at SMPN 34 Kerinci partially is 9.2%. The amount of influence of Interpersonal Communication on Teacher Performance at SMPN 34 Kerinci partially is 9%. The amount of influence of competence on teacher performance at SMPN 34 Kerinci partially is 42.3%. The magnitude of the influence of Organizational Culture, Interpersonal Communication and Competence on Teacher Performance at SMPN 34 Kerinci simultaneously amounted to 60.5%. while the rest (100% - 60.5%) which is 39.5% is explained by other causes which were not examined in this study